2022
DOI: 10.7827/turkishstudies.64602
|View full text |Cite
|
Sign up to set email alerts
|

A Research on E-Health Literacy and Online Health Information Search Behavior

Abstract: This study aimed to determine the e-health health levels of university students studying in the field of health sciences and to examine their online health information seeking behaviors. The research was planned in a descriptive and cross-sectional design. While the population of the research consists of 2012 students of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
1
0
2
Order By: Relevance
“…In the study conducted by Ergün et al (2019) on students, no difference was found between the variables of gender, age, and chronic illness. In the study conducted by Gül, Demir and Çoşkun (2022), no difference was found between the variables of gender, chronic illness and regular drug use. In the study conducted by Yılmaz et al (2020) on university students, no difference was found between gender and age variables.…”
Section: Discussionmentioning
confidence: 85%
“…In the study conducted by Ergün et al (2019) on students, no difference was found between the variables of gender, age, and chronic illness. In the study conducted by Gül, Demir and Çoşkun (2022), no difference was found between the variables of gender, chronic illness and regular drug use. In the study conducted by Yılmaz et al (2020) on university students, no difference was found between gender and age variables.…”
Section: Discussionmentioning
confidence: 85%
“…Sürekli ilaç kullanan bireylerin e-sağlık okuryazarlık puanlarının ilaç kullanmayanlara göre daha yüksek olduğu belirtilmiştir. 31 Bu çalışmada ilaç sayısının artmasıyla online sağlık arama davranışlarının azaldığı görülmektedir. İlaç sayısının fazla olması nedeniyle bireylerin ek tedavi arayışına ihtiyaç duymaması, bilgi arama davranışlarının azalmasına neden olabilir.…”
Section: Discussionunclassified
“…3 Ayrıca kavram; teknolojiyi kullanmayı, e-sağlık kaynaklarını etkin bir şekilde kullanma yeteneğini ve eleştirel düşünmeyi kapsamaktadır. 4 Yüksek düzeyde e-sağlık okuryazarlığına sahip bireyler, sağlıkları ile ilgili bilgileri incelediğinde doğru sonuçlara ulaşmakta ve kendilerini bu bilgiler ışığında yönlendirmektedir. 5 Böylelikle sağlıklı beslenme, yeterli uyku, egzersiz davranışlarının benimsenmesinde ve kronik hastalıkların öz-yönetiminde başarılı olunmaktadır.…”
Section: Introductionunclassified